2015
DOI: 10.1371/journal.pbio.1002171
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Phonemic Contrasts in a Nonhuman Vocal System

Abstract: The ability to generate new meaning by rearranging combinations of meaningless sounds is a fundamental component of language. Although animal vocalizations often comprise combinations of meaningless acoustic elements, evidence that rearranging such combinations generates functionally distinct meaning is lacking. Here, we provide evidence for this basic ability in calls of the chestnut-crowned babbler (Pomatostomus ruficeps), a highly cooperative bird of the Australian arid zone. Using acoustic analyses, natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…We are confident that we can rule out alternative explanations related to a sequential or additive processing of calls, because responses to played back mobbing sequences exceeded those elicited by the independent calls or their sum (33,34). Furthermore, control experiments showed that potential superstimuli (two calls vs. one call) or simple priming effects that could otherwise explain the results can be excluded, because control sequences failed to elicit similar mobbing-like behavior (32,33). In summary, our natural observations combined with the experimental manipulations indicate that babblers produce * * * * * * * * Basic models included all fixed and random effects, intercept models included only the random effects, and best models included only the significant fixed effects based on AICc selection as well as the random effects.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We are confident that we can rule out alternative explanations related to a sequential or additive processing of calls, because responses to played back mobbing sequences exceeded those elicited by the independent calls or their sum (33,34). Furthermore, control experiments showed that potential superstimuli (two calls vs. one call) or simple priming effects that could otherwise explain the results can be excluded, because control sequences failed to elicit similar mobbing-like behavior (32,33). In summary, our natural observations combined with the experimental manipulations indicate that babblers produce * * * * * * * * Basic models included all fixed and random effects, intercept models included only the random effects, and best models included only the significant fixed effects based on AICc selection as well as the random effects.…”
Section: Discussionmentioning
confidence: 83%
“…To rule out alternative explanations associated with the saliency of the stimulus (two vs. one call type) or priming effects (any call type preceding recruitment calls generates the same response), we implemented an additional important control condition, where we artificially replaced the alert call of a mobbing sequence with another acoustically distinct broadband babbler vocalization: the foraging "chuck" call (chuck recruitment sequence) (Supporting Information) (24,32,33). Finally, in line with previous studies (12,13), to ensure that the key dimension for receivers was the combination of information and not any urgency-based acoustic variation encoded across the structure, as an additional control, artificial mobbing sequences were constructed from the independent calls and played back (Supporting Information and Table S1) (13,32). Our playbacks revealed differences in group attentiveness responses to the four playback conditions determined by the proportion of the group that became vigilant (treatment: χ 2 = 53.5; P < 0.01; n = 64; 16 groups) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In general, songs have the dual function of mate attraction and territory announcement and syllable composition may signal male quality (Catchpole and Slater 2003). In another example, chestnut-crowned babblers (Pomatostomus ruficeps) combine two types of notes (A and B) into two sequences (AB or BAB) and use these sequences in different contexts (Engesser et al 2015); they produce AB calls during flight, whereas BAB calls are used in the context of nestling provisioning. Experiments with captive babblers showed that playbacks of AB calls made them look out of the aviary, whereas those of BAB calls made them look at the nest within the aviary.…”
Section: Examples From Birdsmentioning
confidence: 99%
“…Captured babblers were transported by vehicle in bird bags to onsite aviaries (2×2.5×2 m) a few kilometres away and housed with members of the same group (up to three birds per compartment, with vocal contact between adjacent compartments). Captives experienced ambient photoperiods and temperatures and were provided with natural perches and foraging substrate, as well as water and 20 mealworms per bird every 2 h (for further details, see Engesser et al, 2015). Food was withheld after 16:30 h local time.…”
Section: Capture and Housingmentioning
confidence: 99%